Binder-free phenylacrylonitrile/nickel foam electrodes: evaluation electrochemical performance via electron-withdrawing and -donating groups - Al, Mehmet Baver; Yilmaz, Elif Muslu; Eren, Esin; Ozen, Leyla Babali; Ozen, Furkan; Cin, Gunseli Turgut; Oksuz, Aysegul Uygun (Springer, 2026)
This study was focused the electrochemical behavior of 2-(3-chlorophenyl)-3-(4-hydroxyphenyl)acrylonitrile (HPA-mCl) and 2-(4-methylphenyl)-3-(4-hydroxyphenyl)acrylonitrile (HPA-pCH3), incorporating electron-withdrawing and electron-donating substituents, respectively, as potential electrode materials for supercapacitors. Their substituent effects on electrochemical performance were systematically examined, providing insights into how small molecular modifications influence energy storage behavior. The compounds were electrochemically deposited onto nickel foam without any binder to form composite electrodes. Morphological and elemental characterization was performed using scanning electron microscope equipped with energy-dispersive X-ray spectroscopy (SEM-EDS). Electrochemical performance was evaluated through cyclic voltammetry (CV), galvanostatic charge-discharge (GCD), and electrochemical impedance spectroscopy (EIS) analyses. The results showed that the electron-donating (-CH3) group led to higher capacitance, longer charge-discharge times, and lower internal resistance, whereas the electron-withdrawing (-Cl) group enhanced the capacitive mechanism. Notably, the HPA-pCH3 electrode delivered the highest areal capacitance, reaching 36.10 mF cm(-)2 at a current density of 2 mA cm(-)2. In addition, extended cycling stability tests performed using cyclic voltammetry demonstrated that the initial areal capacitance values were 161.98 mF cm(-)2 for HPA-pCH3/NF and 185.50 mF cm(-)2 for HPA-mCl/NF. Both electrodes maintained capacitance retention of 80.9% for HPA-pCH3/NF and 81.8% for HPA-mCl/NF after 3000 cycles, confirming their long-term electrochemical stability. These findings highlight the significant influence of small molecular modifications on energy storage behavior and demonstrate the promise of organic/nickel foam composites for sustainable supercapacitor applications.
Keywords: Energy-Storage; Nickel Foam; Supercapacitor; Oxide